PEDAGOGICAL CONDITIONS FOR DEVELOPING CREATIVE THINKING IN PRIMARY SCHOOL STUDENTS - Zhao, Q (International Journal of Literature and Language Studies, 2026)
Creative thinking is an important educational outcome in primary school because it supports curiosity, imagination, problem solving and independent expression. The aim of this article was to identify pedagogical conditions for developing creative thinking among primary school students. The results show that open-ended tasks, play-based learning, art integration, questioning techniques and supportive classroom climate stimulate originality and cognitive flexibility.